RANKINGS IN BRAZILIAN HIGHER EDUCATION: AN APPROACH TO PUBLIC AND PRIVATE RANKINGS - Calderón, Adolfo Ignacio (2014)
This article provides a theoretical approach to public and private higher education academic rankings in Brazil aimed towards understanding their complexity and course of development. The paper supports that the changes stemming from the transformation from a Provider State into an Evaluator State model strengthened the trends around assessments through rankings, and it also confirms the incipience of private and state rankings faced with a market scenario where they are ultimately legitimized.